BIBLICAL PERSPECTIVE OF THE RUSSIAN INVASION OF UKRAINE IN 2022 - Lawrence Olabode Ekundayo (International Studies Journal)
This paper examined the invasion of Ukraine by Russia from the biblical perspective. The research problem of the paper is the justifications for waging war against a sovereign nation. It is the aim of the paper to investigate the causes of the invasion and the objective is to know the direct effects of the invasion on Nigeria. To achieve our aim and objective, the paper used historical and contextual approaches to assess the position of the Bible on invasion; and also the basis of the Ukrainian invasion. Consequently, the paper discovered the actual reasons for the invasion of Ukraine and those behind it, the internal problem facing Ukraine before the invasion, the potential threat of the invasion to global peace, the actual nation to blame for the invasion and the effects of Russian/Ukrainian war on the Nigerian economy. As a result of these findings, the paper recommended that there must be an immediate demilitarization of Ukraine, NATO's equipment installations on the borders of Russia should be relocated; there must be a restoration of the natural status of Ukraine for the sake of peace, the continuous eastward expansion of NATO must be stopped; and Russian legitimate security interest must be unconditionally taken into consideration by the Western countries to avoid third world war